2005
DOI: 10.1016/j.adolescence.2005.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Self‐image and parental attachment among late adolescents in Belize

Abstract: This study investigated the relationship of ethnicity, parental education, gender, and parental attachment to multiple dimensions of self‐image among 285 (161 female and 124 male) late adolescent Belizean students. Student ratings of self‐image were unrelated to paternal education and student ethnicity. For maternal education, ethnic identity was higher for students whose mothers were high school graduates than for those whose mothers had completed college or a graduate degree. Female students reported more po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Attachment probably also varies across cultures and early research in this arena has suggested that such differences may be discerned (Huiberts, Oosterwegel, Vandervalk, Vollebergh, & Meeus, 2006;Kenny, Griffiths, & Grossman, 2005;Rothbaum et al, 2000;Wang & Mallinckrodt, 2006). Rothbaum et al (2000) compared cultural values from the United States and Japan and argued that tenets of attachment theory reflect values and meaning from Western culture such as secure attachment and the construction of social competence.…”
Section: Attachment and Diverse Culturesmentioning
confidence: 97%
See 1 more Smart Citation
“…Attachment probably also varies across cultures and early research in this arena has suggested that such differences may be discerned (Huiberts, Oosterwegel, Vandervalk, Vollebergh, & Meeus, 2006;Kenny, Griffiths, & Grossman, 2005;Rothbaum et al, 2000;Wang & Mallinckrodt, 2006). Rothbaum et al (2000) compared cultural values from the United States and Japan and argued that tenets of attachment theory reflect values and meaning from Western culture such as secure attachment and the construction of social competence.…”
Section: Attachment and Diverse Culturesmentioning
confidence: 97%
“…College students in Belize were surveyed by Kenny et al (2005). These late adolescents demonstrated that favorable self-images were related with secure ratings of parental attachment.…”
Section: Attachment and Diverse Culturesmentioning
confidence: 98%
“…Higher self image has been associated with secure attachment style (Kenny et al 2005;O'Koon 1997). Higher BMI, in turn, has been found to be associated with lower self image (Davison and Birch 2002;Riley et al 1998) and decrease in self image over time (O'Dea 2006).…”
mentioning
confidence: 99%
“…In one of them the coping aspect of the self-image was also found significantly related with secure attachment (O'Koon's, 1997). In the other, similarly, self-confidence and social functioning scales evidenced a significant positive association with a continuous measure of attachment security (Kenny et al, 2005).…”
Section: Discussionmentioning
confidence: 84%
“…In a study examining the relationship between adolescents' attachment styles and self-image, O'Koon (1997) found that secure attachment to parents was significantly related with the coping aspects of self-image, and secure attachment to peers was significantly related to, particularly, body-image, vocational goals, and the sexual attitude aspects of the self-image. Similarly, in another study examining the relationship of self-image and parental attachment among late adolescents (Kenny, Griffiths, & Grossman, 2005) it was found that secure parental attachment was associated with positive views of self across multiple domains. Aside from these studies the relation of attachment styles to selfimage has not been largely researched.…”
mentioning
confidence: 88%